The Phenomenon of Alienation in The Paintings of European Artists in The Eighteenth and Nineteenth Centuries - Fatemeh Mustafa Ibrahim; Ari Kakil Mohmedtaher (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Conducting research about the topic of alienation is of great importance since alienation is one of the main aspects reflected in artists’ works. Alienation is one of the most important psychological phenomena that has impacted artistic productions throughout history. Especially after the Renaissance in Europe, after the industrial revolution philosophers, psychologists, and artists paid more attention to the topic. Alienation has been reflected in the literature of the eighteenth and nineteenth centuries as well as in the paintings of those centuries. Similar to authors, artists focused on the topic of alienation and conveyed it through their paintings. This research focuses on the topic of (phenomenology of alienation in the works of eighteen and nineteenth-century artists in Europe) and consists of four sections. The first section includes the importance of the research, the second section includes theoretical framework (1. phenomenology of alienation in art 2. Emergence of alienation in Europe art 3. Aspects of alienation phenomena in the art of Europe). The third section consists of research methodology and sample analysis.